HOL Design with Natural Process of Khmer-Thai Ethnics Group in Cultural Ecology of Lower Mekong Basin - Tungprasit, Prasong; Chunkao, Kasem; Phanurat, Achara; Udomthawee, Kotchanipha (Mediterranean Journal of Social Sciences, 2012)
The research design was mixed methods of quantitative and qualitative approaches. The research design for qualitative research was In-Dept Interview with structural form with 70 peoples comprised 50 Thai, 20 Khmer and 5 experts and quantitative research was survey research with 500 peoples of Khmer-Thai ethnics group who involved in natural dyeing silk. The content from qualitative research was analyzed to construct the questionnaire for quantitative research. Factor analysis was used for determination the component factors. The objectives of this research were to study cultural ecology of herb related to Hol silk cloth handicraft and to analyze component factor of dyeing silk with Hol design with natural process of Khmer-Thai ethnics group. The finding illustrated that there were 58 items were constructed from content analysis of In-Depth Interview and there were 6 components comprising 1) Hol Design with Natural Dyeing to Support Environment and Cultural Ecology, 2) Secret Code of Buddhist and Royal Household Wisdoms Succeeded Transferring of Fasten Dyeing and Hol Cloth Weaving Process, 3) Local Science and Technology Cultivated at Child Age through Family Learning, 4) Sun Energy and Water Mixers with Natural Process Conserve Ecosystem, 5) Content of Environmental Knowledge for Value Change of Chemical Use, and 6) Local Plants and Herbs are Important Raw Material of Sufficient Life with Local Appropriate Technology